Stereocontrolled synthesis of the C8-C22 fragment of rhizopodin - Kretschmer, Manuel; Menche, Dirk (Organic letters, 2012)
A convergent synthesis of the central C8-C22 core of the potent macrolide antibiotic rhizopodin is reported. Notable features of the stereocontrolled approach include an asymmetric reverse prenylation of an alcohol using a method of Krische, a thiazolium catalyzed transformation of an epoxyaldehyde as described by Bode, and a late-stage oxazole formation from advanced intermediates. This route demonstrates the applicability of these methodologies in complex natural product synthesis.
Published online: December 13, 2011
Gesehen am 26.04.2018